2019
DOI: 10.1136/bmjgh-2019-001837
|View full text |Cite
|
Sign up to set email alerts
|

The burden of anaemia among displaced women and children in refugee settings worldwide, 2013–2016

Abstract: IntroductionDisplaced persons have a unique risk for developing anaemia due to often limited diets, overcrowding, new infections and inadequate sanitation and hygiene. The lack of anaemia prevalence estimates among the displaced inhibit global planning for anaemia reduction.MethodsWe analysed population representative, cross-sectional nutrition surveys from 2013 to 2016 conducted by the United Nations High Commissioner for Refugees and partner agencies. Included surveys measured haemoglobin concentration among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
0
16
0
4
Order By: Relevance
“…Anaemia prevalence is common around the globe but most prevalent in developing countries. Prevalence of anaemia was recorded higher in the South Asian and African continent than in other countries throughout the world (Ajepe et al, 2020).Global estimation indicated that three out of ten (29%) of non-pregnant women and more than one third (38%) were anaemic (Herzog et al, 2019;Kay et al, 2019). It is estimated that nearly half a billion of women from reproductive age are affected by anaemia (Wemakor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia prevalence is common around the globe but most prevalent in developing countries. Prevalence of anaemia was recorded higher in the South Asian and African continent than in other countries throughout the world (Ajepe et al, 2020).Global estimation indicated that three out of ten (29%) of non-pregnant women and more than one third (38%) were anaemic (Herzog et al, 2019;Kay et al, 2019). It is estimated that nearly half a billion of women from reproductive age are affected by anaemia (Wemakor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite low dietary contribution of Ethiopian okra to the RDA for Fe, less than 15% for young children and pregnant women, this still may have some positive nutritional implications given the huge prevalence of Fe deficiency during pregnancy in SSA particularly in a refugee setting. For example, in 2008, anemia was the cause for 55% of maternal deaths in Daddab refugee camp in Kenya [ 116 ] and continues to exert maternal mortality in humanitarian crisis [ 117 ]. Likewise, Andresen et al [ 118 ] found high overall prevalence of anemia among South Sudanese children aged between 6 and 59 months in Kule (51.9%) and Tierkidi (46.2%) refugee camps in Ethiopia, a value slightly higher than the demonstrated prevalence was obtained for South Sudanese children of similar ages residing in Pugnido refugee camp in Gambella region, Ethiopia [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neben Infektionskrankheiten gibt es andere Erkrankungen und Gesundheitsprobleme, die gehäuft bei minderjährigen Flüchtlingen auftreten und dadurch auch in der Untersuchung besondere Beachtung erfahren sollten. Beispiele sind die sehr häufig feststellbaren Zahnerkrankungen [ 8 ] sowie Anämien [ 12 ]. Insbesondere bei UMF treten gehäuft psychische Erkrankungen auf [ 13 , 14 ].…”
Section: Allgemeine Untersuchung Bei Ankunft Und Im Verlaufunclassified